Widespread morphea. A case treated with factor XIII. - Menni, S.; Marzano, A.; Passoni, E. (European Journal of Pediatric Dermatology, 2018)
An 11-year-old girl with widespread and progressive localized cutaneous scleroderma was treated with factor XIII. The treatment was responsible for moderate improvement of the cutaneous lesions. This treatment has been until now used in systemic sclerosis and in generalized cutaneous scleroderma. However, given the lack of side effects, the treatment can be used, according to the Authors, even in cases of localized cutaneous scleroderma affecting exposed areas or rather extensive.